Adjunctive Therapies for Treatment of Severe Respiratory Failure in Newborns - Patry, C.; Hien, S.; Demirakca, S.; Reinhard, J.; Majorek, M.; Brade, J.; Schaible, T. (Klinische Pädiatrie, 2015)
Background: Severe respiratory failure of the newborn requires adjunctive therapies as application of surfactant, inhalation of nitric oxide (iNO), high frequency oscillatory ventilation (HFOV), or extracorporeal membrane oxygenation (ECMO). We designed this study to analyze the the usage and effectiveness of adjunctive therapies and the mortality of severe respiratory failure.Patients and Methods: The survey in Germany was done in collaboration with the “Erhebungseinheit für seltene pädiatrische Erkrankungen” (ESPED). 397 patients within 2 years were included into the study. Effectiveness of each adjunctive therapy was judged by the treating physician.Results: The most frequent diagnosis was respiratory distress syndrome (RDS) with 36.8%, followed by pneumonia sepsis (16.4%), meconium aspiration syndrome (MAS) and congenital diaphragmatic hernia (CDH). Surfactant was applied in 77.3% of all cases with a reported effectiveness of 71.6%. More than 40% of all patients were treated with iNO, which led to an improvement in every second case. HFOV was used in every third case with a response rate of about 60%. ECMO was performed on one in 7 patients and was sucessful with a survival rate of nearly 80%. The overall mortality was 10.3%. 29 patients in total died without ECMO. 10 of them might actually have been contraindicated, but 19 cases with a potential benefit from ECMO were not transferred for ECMO.Conclusion: Our study-data suggests that more newborns suffering from respiratory failure should be transferred to centers offering ECMO.
Keywords: adjunctive therapies; ECMO; mortality; term or near term newborns